THE EFFECT OF LIFESTYLE AND REFERENCE GROUPS ON E-CIGARETTE PURCHASING DECISIONS - Nyoko, Antonio E. L.; Fanggidae, Ronald P. C.; Haumetan, Fransiskus (Universitas Nusa Cendana, 2024)
This study aimed to investigate the effect of lifestyle and reference groups on e-cigarette consumer purchasing decisions in Kupang City. Convenience sampling was employed as the sampling strategy and the questionnaire was utilized to obtain the data. Multiple linear regression analysis was used to identify the changes of independent variables on the dependent variable in the data analysis. The hypothesis test was performed to test the effect of the significance of independent variables on the dependent variable. The findings of this study indicate that lifestyle has no positive and significant influence on the purchasing decision of e-cigarettes, reference groups have a positive and significant impact on e-cigarette purchasing decisions, and lifestyle and reference groups simultaneously have a positive and significant effect on the purchasing decision of e-cigarettes in Kupang city. It is suggested to study further other consumer behavior personal factors such as job and economic conditions that might moderate or mediate the relationship between lifestyle or reference groups toward consumers' purchasing decisions. Keywords: Lifestyle; References Groups; Purchasing Decisions; e-Cigarette